NFX1, Its Isoforms and Roles in Biology, Disease and Cancer - Sreenivasulu Chintala (Biology, 2021)
In 1989, two NFX1 protein products were identified as nuclear proteins with the ability to bind to X-box cis-elements. Since that publication, the NFX1 gene and its homologs have been identified, from yeast to humans. This review article summarizes what is known about the NFX1 gene across species. We describe the gene and protein motifs of NFX1 homologs and their functions in cellular biology, then turn to NFX1 in human biology and disease development. In that, we focus on more recent literature about NFX1 and its two splice variants protein products (NFX1-91 and NFX1-123) that are expressed in epithelial cells. We describe new evidence of conserved protein motifs, direct and indirect gene expression regulation, and critical protein-protein interactions. Finally, we stress the emerging roles of these NFX1 splice variants in high-risk human papillomavirus-associated cancers, and the increased expression of the longer splice variant, NFX1-123, found in these cancers.